Manifestations of malaria: a clinical experience - S., Prabhu; V. N., Prashanth (International Journal of Advances in Medicine, 2018)
Background: Malaria is fast emerging as a number one infectious disease with high morbidity and mortality across the globe. It’s being transmitted across 108 countries containing 3 billion populations (40% of world’s populations) with more than 3 million deaths per year. India is an endemic country for malaria with an estimated 70-100 million1 cases per year. 45-50% of them are due to Plasmodium falciparum (Pf). Pf is responsible for majority of severe and fatal malaria though death due to Plasmodium vivax mono infection have also been reported. Symptoms and sign are highly non-specific in malaria making it more of a clinical diagnosis more than a laboratory diagnosis. Presentation may vary at times and can be quite confusing as malaria is a multisystem disease. Authors’ idea was to study the variable manifestations in confirmed cases of malaria patients at our hospital Methods: A hospital based cross sectional study was conducted for a period of one year-from 01-08-2015 to 31-07-2016 based on authors’ hospitals records (case sheets with demography profile, clinical features, investigations and treatment outcome). Results: A total of 369 patients positive for malaria parasite were included in the study. 369 were smear positive-219 positive for Plasmodium vivax, 127 were P. falciparum type and 23 were for both. Majority were males (64.50%) and belonged to the age group of 21-50 years (58.84%). They were admitted in post monsoon months (60.43%). Of them 46.44% had classical symptoms of malaria. All the patients had received mainly artemisinin combination therapy (ACT) and 91.87% patients recovered in 7-28 days. The mortality rate was nearly 5.69%. Conclusions: The present study was useful to know the varied manifestations of malaria and hence will be useful in making a clinical diagnosis of malaria.